26th Annual Conference of the International Group for Lean Construction 2018
DOI: 10.24928/2018/0500
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Value of an Effective Collaborative Decision-Making Process in the Design Phase

Abstract: Decisions are the foundation for creating value in a project. Particularly in the early design phases, decisions form and restrict the value creation processes throughout the project's life cycle Therefore, project teams should pay attention to the decision-making process, and design it to secure maximum value creation and clear documentation. This paper shows and analyses the decision-making process in the design phase of four different projects based on four characteristics: (1) decision-making method, (2) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…In the case of the socioemotional activities, the highest and lowest scores did not show any evidence of being impacted by gender. a shared understanding and trustful environment (Schöttle et al 2018). The literature has not yet studied whether CBA encourages inclusiveness with regard to the three issues we have studied in the literature.…”
Section: Choosing By Advantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the socioemotional activities, the highest and lowest scores did not show any evidence of being impacted by gender. a shared understanding and trustful environment (Schöttle et al 2018). The literature has not yet studied whether CBA encourages inclusiveness with regard to the three issues we have studied in the literature.…”
Section: Choosing By Advantagesmentioning
confidence: 99%
“…Construction projects contain a series of team decisions, including strategic decisions, because they affect different parties. Although decision-making is key for project progress, group decisionmaking is not thoughtfully designed in projects (Schöttle et al 2018). Often responsibility, structure, documentation, reporting and time track are not defined upfront, making it difficult for the team to decide and receive decisions on time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that using the Tabular method leads to productive conversation, because of less tangential discussions (Arroyo and Long 2018), results in constructive debates, less misinterpretation, and a transparent documentation that is traceable for a party not involved in the decision-making (Schöttle and Arroyo 2017). Furthermore, teams achieved faster consensus and felt less frustration during decision-making when using CBA in comparison to scoring systems (Arroyo et al 2016) and felt more confident about the decision quality (Schöttle et al 2018).…”
Section: Background Literature Review Choosing By Advantagesmentioning
confidence: 99%
“…The term collaboration is sometimes confused with cooperation. Schöttle et al (2018) examined the difference between these two terms in an LC context and found that the relationship between project actors is stronger in collaboration than in cooperation. In both terms, the actors are dependent on other actors to reach their goals.…”
Section: Introductionmentioning
confidence: 99%